PENDIDIKAN ISLAM ANTARA CITA DAN FAKTA: Konsep Pengembangan Pendidikan Islam dalam Perspektif Muhammad Iqbal - Ayyub AR (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
Iqbal states that Islamic education should cover the human totality. Therefore, Islamic education put stress in a maximum action and creativity for human growth and development physically and mentally. The goal of Islamic education is to train individual to be good so that they can actualize himself to be a creative person with full of faith. To catch the reality is from reflective observation and intuition process or â€œloveâ€ called heart observation. The achievement of this process is callled by Iqbal as metaphysic knowledge.